Effect of pelleting on the recalcitrance and bioconversion of dilute-acid pretreated corn stover under low- and high-solids conditions. Issue 3 (May 2013) - Ray, Allison E; Hoover, Amber N; Nagle, Nick; Chen, Xiaowen; Gresham, Garold L
Background: Knowledge regarding the performance of densified biomass in biochemical processes is limited. The effects of densification on biochemical conversion are explored here.Results: Pelleted corn stover samples were generated from bales that were milled to 6.35 mm. Low-solids acid pretreatment and simultaneous saccharification and fermentation were performed for pelleted and ground stover (6.35 and 2 mm) formats. Monomeric xylose yields were significantly higher for pellets (∼60%) than for ground formats (∼38%). Pellets achieved approximately 84% of theoretical ethanol yield; ground stover formats had similar profiles, reaching approximately 68% theoretical ethanol yield. Pelleted and 6.35-mm ground stover were evaluated using a ZipperClave® reactor under high-solids, process-relevant conditions for multiple pretreatment severities (Ro ); feedstock reactivity increased slightly following combined pretreatment and enzymatic hydrolysis for three of five severities tested.Conclusion: Pelleting did not render corn stover more recalcitrant to dilute-acid pretreatment under low- or high-solids conditions, and even enhanced ethanol yields.